Polygenic risk score for embryo selection—not ready for prime time. Issue 10 (19th July 2022) - Polyakov, Alex; Amor, David J; Savulescu, Julian; Gyngell, Christopher; Georgiou, Ektoras X; Ross, Vanessa; Mizrachi, Yossi; Rozen, Genia
Abstract: Numerous chronic diseases have a substantial hereditary component. Recent advances in human genetics have allowed the extent of this to be quantified via genome-wide association studies, producing polygenic risk scores (PRS), which can then be applied to individuals to estimate their risk of developing a disease in question. This technology has recently been applied to embryo selection in the setting of IVF and preimplantation genetic testing, with limited data to support its utility. Furthermore, there are concerns that the inherent limitations of PRS makes it ill-suited for use as a screening test in this setting. There are also serious ethical and moral questions associated with this technology that are yet to be addressed. We conclude that further research and ethical reflection are required before embryo selection based on PRS is offered to patients outside of the research setting.